A feed-forward spiking model of shape-coding by IT cells - Romeo, August; Supèr, Hans (Frontiers in Psychology, 2014)
The ability to recognize a shape is linked to figure-ground organization. Cell preferences appear to be correlated across contrast-polarity reversals and mirror reversals of polygon displays, but not so much across figure-ground (FG) reversals. Here we present a network structure which explains both shape-coding by IT cells and the suppression of responses to figure-ground reversed stimuli. In the model figure-ground discrimination is achieved much before shape discrimination, that is itself evidenced by the difference in the spiking onsets of a couple of cells selective for two image categories.